Academic Achievement and Social Interactions: A Longitudinal Analysis of Peer Selection Processes in Inclusive Elementary Classrooms - Garrote, Ariana (Frontiers in Education, 2020)
This study analyzes the extent to which students in inclusive elementary classrooms select classmates for collaboration and play activities on the basis of academic achievement. To investigate this association, second and third graders (n = 506, mean age 7.6 years) were asked to nominate classmates with whom they collaborate and play at the beginning and middle of the school year. The academic achievement level of students was assessed with a standardized mathematical test at the first measurement point. Two longitudinal social network models were specified to analyze whether academic achievement level functions as a selection criterion for collaboration (academic context) and play activities (play context). Structural network effects, selection effects, and sex-related effects were included in the models. The selection effects on academic achievement revealed that high achieving students were more likely selected by peers for collaboration but not for play activities. Thus, academic achievement was only relevant for peer selection processes in the academic context. Further, a negative homophily effect on academic achievement was found, which indicates that students selected dissimilar peers in terms of academic achievement level for interactions in the academic and play context. Thus, on one hand there was no similarity in academic achievement among peers who liked to collaborate and play together, which is a positive result from an educational and inclusive perspective; on the other hand, there was a tendency to select high achieving rather than low achieving peers for collaborative activities. Teaching practices that can help prevent the formation of such a hierarchy in the classroom and implications for future studies on the link between academic achievement and peer selection processes are discussed.